Expression of the fluorescent reporter genes GFP and dsred in Aspergillus oryzae VS1 strain using Agrobacterium tumefaciens-mediated transformation - Quynh, Ho Ngoc; Khuyen, Nguyen Thi; Phuong, Tran Thi; Tuan, Tran Van (Academia Journal of Biology, 2017)
Aspergillus oryzae is a filamentous fungus commonly used in industrial production of food and beverages in Vietnam and other Asian countries. Due to its safety and high secretion ability, this fungus has been widely exploited for production of recombinant proteins and enzymes. However, A. oryzae transformation is still mainly performed via fungal protoplasts using a complicated and costly procedure. Recently, using the auxotrophic AUT1-PlD strain provided by the University of Tokyo, Japan, our research group has successfully developed an optimized procedure of Agrobacterium tumefaciens-mediated transformation (ATMT) for A. oryzae. In this study, we have confirmed that this ATMT method with the pyrG marker is working well for another A. oryzae strain (VS1) isolated in Vietnam. This strain is non-aflatoxigenic, fast-growing and represents a good capacity of extracellular enzyme secretion. Our results indicated that the transformation efficiency of the auxotrophic VS1 strain is approximately 100 times higher than that of the AUT1-PlD strain originated from Japan. With this transformation method, the fluorescent reporter genes GFP and DsRed have been successfully integrated into the genome of the VS1 strain resulting in their strong expression in the fungal mycelia and conidiophores.   Citation: Ho Ngoc Quynh, Nguyen Thi Khuyen, Tran Thi Phuong, Tran Van Tuan. Expression of the fluorescent reporter genes gfp and dsred in Aspergillus oryzae vs1 strain using Agrobacterium tumefaciens-mediated transformation. Tap chi Sinh hoc, 39(2): 212-222. DOI: 10.15625/0866-7160/v39n2.8955. *Corresponding author: tuantran@vnu.edu.vn Received 11 December 2016, accepted 20 March 2017